2022
DOI: 10.1029/2022gl099793
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Hurricane Intensification Rate Near the US Atlantic Coast

Abstract: Hurricanes often cause severe damage and loss of life, and storms that intensify close to the coast pose a particularly serious threat. While changes in hurricane intensification and environment have been examined at basin scales previously, near‐coastal changes have not been adequately explored. In this study, we address this using a suite of observations and climate model simulations. Over the 40‐year period of 1979–2018, the mean 24‐hr hurricane intensification rate increased by ∼1.2 kt 6‐hr−1 near the US A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 80 publications
(96 reference statements)
2
41
3
1
Order By: Relevance
“…The CMIP6 multimodel ensemble suggests that wind shear will likely reduce near the East Coast of the United States and the northern Gulf of Mexico (Fig. 5A), in line with several previous studies ( 24 , 25 , 28 , 29 ). When the SWM is forced by simultaneous changes in basic states, diabatic heating, and transient eddies, it broadly reproduces the spatial pattern of wind shear responses over the North Atlantic and the eastern Pacific (Fig.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The CMIP6 multimodel ensemble suggests that wind shear will likely reduce near the East Coast of the United States and the northern Gulf of Mexico (Fig. 5A), in line with several previous studies ( 24 , 25 , 28 , 29 ). When the SWM is forced by simultaneous changes in basic states, diabatic heating, and transient eddies, it broadly reproduces the spatial pattern of wind shear responses over the North Atlantic and the eastern Pacific (Fig.…”
Section: Resultssupporting
confidence: 90%
“…5D). Thus, in addition to altering the steering flow, future changes in diabatic heating could lead to increases in hurricane intensification (24,25) and tropical cyclogenesis (34) near the U.S. coast through the influence on wind shear, highlighting the broad implication of the mechanism identified in this study. Nevertheless, the projected decrease in translation speeds over the subtropical North Atlantic (Fig.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Given that atmospheric and oceanic features vary across the Atlantic basin, TC intensification rates and their relationships with environmental variables may also vary by region. Their trends may vary by region too, and there is scope to build on Balaguru et al (2018Balaguru et al ( , 2022 and Bhatia et al (2022) to reveal new regional relationships. To date, no studies have investigated observed regional trends using probability density functions (PDFs) of TC-relative environmental variables, for RI versus slower intensification.…”
mentioning
confidence: 99%